2021
DOI: 10.3390/ma14237309
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Hybrid Complex of Cyclodextrin-Based Metal—Organic Frameworks-1 and Ascorbic Acid Derivatives

Abstract: Cyclodextrin-based metal–organic frameworks-1 (CD-MOF-1) prepared using potassium hydroxide, ethanol, and γ-cyclodextrin (γ-CD) has been reported as a new type of MOF for the development of pharmaceutical formulations. The present study aimed to investigate the physicochemical properties of ascorbic acid derivatives (L-ascorbyl 6-palmitate (ASCP); L-ascorbyl 2,6-palmitate (ASCDP)) complexed with CD-MOF-1 by a solvent evaporation method. Powder X-ray diffraction revealed that the crystal diffraction pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Metal-organic frameworks based on cyclodextrins (CD-MOF) are biocompatible crystalline structures with a highly developed specific surface area. Due to the presence of pores of different diameter, CD-MOFs are able to accommodate various substances, acting not only as carriers, but also as an effective solubilizers [ 11 , 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. For example, it has been demonstrated that γ-CD-based MOFs (γCD-MOF) can serve as superior carriers for curcumin [ 17 , 18 ], ascorbic acid derivatives [ 19 ], hexanal [ 20 ], methotrexate [ 21 ], and leflunomide [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks based on cyclodextrins (CD-MOF) are biocompatible crystalline structures with a highly developed specific surface area. Due to the presence of pores of different diameter, CD-MOFs are able to accommodate various substances, acting not only as carriers, but also as an effective solubilizers [ 11 , 12 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. For example, it has been demonstrated that γ-CD-based MOFs (γCD-MOF) can serve as superior carriers for curcumin [ 17 , 18 ], ascorbic acid derivatives [ 19 ], hexanal [ 20 ], methotrexate [ 21 ], and leflunomide [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The articles catalogued in Table 3 primarily center on MOF-based transdermal systems as a potential remedy for melanoma and an array of wounds such as diabetic, chronic, and infected wounds. CD-MOFs have shown to be able to encapsulate various drugs and active compounds, including doxorubicin, 176,177 resveratrol, 140,178 epigallocatechin gallate, 179 vitamin A palmitate, 180 ascorbic acid derivatives, 181 myricetin, 182 ketoconazole, 183 salicylic acid, 140 ferulic acid, 140,163 different NSAIDs, 184 emodin and quercetin. 128…”
Section: Efficacy Of Cd-mof Transdermal Drug Delivery Systemsmentioning
confidence: 99%
“…The 1 H CPMAS NMR and 13 C CPMAS NMR were employed to further investigate the host−guest interaction sites between eugenol and CD-MOF-1 by using an AVANCE NEO 600 MHz SS NMR instrument (Bruker AXS GmbH, Karlsruhe, Germany).…”
Section: Cross-polarization Magic Angle Spinning (Cpmas) Nmrmentioning
confidence: 99%
“…The primary change of γ-CD unit cavity before and after introducing eugenol is due to potential host−guest attractions. The 1 H liquid-state (LS) NMR and 13 C solid-state (SS) NMR spectra were employed to further investigate intermolecular interactions of eugenol and CD-MOF-1. Based on the 1 H LS NMR result, each γ-CD unit carried 0.87 eugenol calculated by the integration ratio of the peak at 5.03 ppm (−C1−H, doublet) from the γ-CD unit of CD-MOF-1 and the chemical shift at 5.94 ppm (�CH−, multiplet) from eugenol (Figure S22).…”
Section: Antibacterial 321 Adsorption Of Antibacterialmentioning
confidence: 99%
See 1 more Smart Citation